Truth and Reconciliation through web design: Integrating Indigenist and Western approaches to teaching writing on a writing centre website - Bell, Theresa; Keenan, Caitlin; Faerber, Jonathan (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
We explore relationality and decolonization within the context of our shared attempts to blend Indigenist (Wilson & Hughes, 2019) and Western approaches to information sharing on a redesigned writing centre website. To reflect and honour the importance of story-telling in Indigenous ways of knowing and being, our core discussion is framed as a conversation that is experiential, reflective, and relational. We explain how the redesigned website supports students’ learning about themselves as academic storytellers through invitational, meaningful, personal online experiences. By telling the story of where the project started and our motivations, choices, emotional experiences, and lessons learned, we articulate an actionable, broadly adaptable pedagogical approach to decolonizing academic writing support.